A General Equilibrium Theory of Occupational Choice under Optimistic Beliefs about Entrepreneurial Ability - Michele Dell'Era; Luca David Opromolla; Luís Santos-Pinto (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper studies the impact of optimism on occupational choice using a general equilibrium framework. The model shows that optimism has four main qualitative effects: it leads to a misallocation of talent, drives up input prices, raises the number of entrepreneurs, and makes entrepreneurs worse off. We calibrate the model to match U.S. manufacturing data. This allows us to make quantitative predictions regarding the impact of optimism on occupational choice, input prices, the returns to entrepreneurship, and output. The calibration shows that optimism can explain the empirical puzzle of the low mean returns to entrepreneurship compared to average wages.
Keywords: D50; H21; J24; L26; 330; general equilibrium; entrepreneurship; optimism